PENGARUH TINGKAT PENDIDIKAN, PENGETAHUAN AKUNTANSI DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN UMKM (STUDI PADA UMKM KECAMATAN KALIDERES) - Atikah Hijriyanah; Harti Budi Yanti (EBID: Ekonomi Bisnis Digital, 2023)
The aim of this research is to study how the level of education, accounting knowledge, and use of information technology affect the quality of financial reports of small and medium enterprises (MSMEs). This research involved 460 MSMEs in Kalideres, and 40 respondents were selected as data samples. This research was conducted using quantitative methods. The IBM SPSS Statistics 25 application is a program used to analyze data. The research results show that the quality of financial reports is not influenced by the level of education; On the contrary, accounting knowledge using information technology has a positive effect on the quality of financial reports.